Система криптографічного захисту bluetooth зв’язку симетричним алгоритмом блокового шифрування - Корсун, Д. М. (ХНУРЕ, 2023)
This work is devoted to the study of data protection in the Bluetooth channel in modem IoT devices. Bluetooth 4.0 and above have addressed security issues by implementing the Security Manager, responsible for authentication, security, confidentiality, and privacy protocols. The Security Manager uses AES, a 128-bit symmetric block cipher, as the encryption key algorithm in the latest Bluetooth versions. The goal is to describe the block encryption method for transmitting data packets between devices using Bluetooth.